Delivery models for climate information in East and West Africa - Jost, Christine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
This study is a survey of existing and emerging models for the delivery of agricultural information to rural communities in CCAFS countries in East and West Africa. The objective is to identify promising frameworks on which to build for the delivery of climate information to rural communities, understand gaps in current distribution networks, identify factors that may prevent poor farmers from accessing or using climate information, and identify other kinds of support that poor farmers need for climate information to be of use.